Analisis Tingkat Kepuasan Pasien terhadap Pelayanan Petugas Rekam Medis di Tempat Pendaftaran Pasien Rawat Inap RSUD Batang - Chusnul Marom; Endah Widaningtyas; Nur Asia Hapsari Pratiwi; Nasrul Lathif (EMVIRO Jurnal Ilmiah Penelitian Kesehatan, 2024)
The Inpatient Registration Place (TPPRI) at Batang Regional Hospital plays a crucial role in managing the reception and registration of patients requiring hospitalization. TPPRI officers are essential in providing services, including the speed of service, room assignment, and necessary facilities for inpatients. Common issues include disputes over room availability, patients using connections to prioritize their admission, and incomplete BPJS patient files at the time of registration. Additionally, some BPJS patients discover their membership status is no longer active during registration. This study aims to assess patient satisfaction with the medical record officers’ services at TPPRI using a quantitative, descriptive approach. Data were collected through interviews with officers and surveys for patients who registered at the hospital. The study's population is the average number of patients hospitalized in one month. The data analysis employed univariate analysis to determine patient satisfaction across five dimensions: Tangibles, Reliability, Responsiveness, Assurance, and Empathy, using SPSS software. Results showed that in the Tangibles dimension, 57.14% of patients were satisfied; in the Reliability dimension, 51.65% were quite satisfied; in the Responsiveness dimension, 52.75% were quite satisfied; in the Assurance dimension, 53.85% were quite satisfied; and in the Empathy dimension, 83.52% were satisfied. In conclusion, patient satisfaction with the medical record officers at Batang Regional Hospital is categorized as quite satisfied in three dimensions and satisfied in two dimensions.